PENINGKATAN KAPABILITAS GURU DAN KARYAWAN SMAN 7 SURAKARTA DALAM MANAJEMEN KONTEN WEBSITE OPEN SOURCE - Aisyah Mutia Dawis (Universitas 'Aisyiyah Surakarta, 2021)
Over time, Information Technology has become more advanced and has made the public to be literate towards technology, especially educational staff who must continue to provide knowledge to their students. Blog or weblog is a term used to describe a development of a personal website that makes it easy for users to display personal information on the Internet in an easy way. However, not all employees and teachers at the school are able to manage content from the website, one of which is SMAN 7 Surakarta. This is due to the lack of counseling in managing the content of this website. From the description above, we are interested in doing community service entitled â€œImproving the Capabilities of Teachers and Employees of SMAN 7 Surakarta in Open Source Website Content Management.â€